Training and assistance processing of corn and peanut based food products - Zainal Abidin; Hironnymus Jati; Titik Sri Harini; Lewi Jutomo (Community Empowerment, 2023)
The aim of the PPDM is to increase partners' knowledge and skills in processing food made from corn and peanuts as well as knowledge of distribution permits. In addition, it also improves the quality and selling value of processed products with appropriate technology with BUMD Sillau Raya and expands the marketing network. The program carried out with the dissemination of appropriate technology, counseling, training, assistance in processing corn and peanuts, assistance in product testing, and obtaining distribution permits. The results of this program are increasing knowledge about the importance of having a distribution permit, processing food production processes more effectively and efficiently with appropriate technology, and certified and halal-labeled products.